Driving Transformative Learning within Australian Indigenous Studies. Issue 1 (August 2019) - Bullen, Jonathan; Roberts, Lynne
Abstract : Australian undergraduate programmes implementing Indigenous studies courses suggest transformative educational outcomes for students; however, the mechanism behind this is largely unknown. To begin to address this, we obtained baseline data upon entry to tertiary education (Time 1) and follow-up data upon completion of an Indigenous studies health unit (Time 2) on student learning approaches, student-teacher rapport, classroom community, critical reflection (CR) and transformative experiences within the unit. Three-hundred-thirty-six health science first-year students (273 females, 63 males) completed anonymous in-class paper questionnaires at both time points. Hierarchical multiple regression analysis indicated that (a) CR was the strongest predictor of transformative learning experiences, (b) the relationship between deep learning approach upon entry to tertiary education and transformative learning experiences was mediated by CR and (c) rapport and classroom community accounted for significant variance in CR. These results suggest that students benefit from tutors' ability to develop rapport and classroom community, leading to greater capacity for student CR. This in turn promotes transformative learning possibilities within the Indigenous studies learning environment. These findings provide a further rationale for institutions to embed Indigenous knowledge into courses and highlight the importance of evaluating their effect and quality.